Обоснование и анализ структурной схемы синтезатора частоты в качестве возбудителя рефлектометра - Борохов, Иван Валерьевич; Мороз, Александр Николаевич (Eastern-European Journal of Enterprise Technologies, 2011)
Substantiates the structural scheme and made the analysis of digital frequency synthesizer as the causative agent scatterometer for remote sensing of biological objects